Maqasid al-shariah as a parameter for islamic countries in screening international treaties before ratification: An analysis - Mohd Lotpi, Mohd Yusob; Lily Suryati, Mohd Jamil; Khairun-Nisaa, Asari (Universiti Putra Malaysia, 2015)
Research into Maqasid al-Shariah (objectives of Islamic Law) has been conducted since the era of al-Juwaini and al-Ghazali. Islamic scholars today try to accommodate the application of Maqasid al-Shariah in a plethora of complex and complicated issues. Generally, the essence of Maqasid al-Shariah is to avoid evil and uphold public interest. Maqasid al-Shariah is important because the law or rules (hukm) will only be effective among Muslims and acceptable in the eyes of God if they are made within the purview of Maqasid al-Shariah. As members of the modern world community, it is inevitable that Islamic countries will need to participate in international treaties. However, there are several provisions in international treaties that may not commensurate with Maqasid al-Shariah. Islamic countries that tend to uphold the principles of Shariah have to ensure that every law, including international treaties, observes the principles of Maqasid al-Shariah in order to make such laws effective and acceptable as mentioned above. This paper, therefore, aims to analyse the essence of Maqasid al-Shariah and use it as a parameter for Islamic countries to participate in international treaties. This parameter can be a guideline for Islamic countries as to whether to consent, reserve or object to provisions in international treaties.